Teknik Pembelajaran Kosa Kata Bahasa Arab Dengan Multimedia - Nisa', Beta Fadiatun; Nurhidayati, Anin; Mufidah, Luk-Luk Nur (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
Vocabulary is a basic element for foreign language learners to acquire proficiency in the language. Language learners need to design effective learning techniques so that vocabulary mastery can be optimal. The majority of language teachers use the technique of translating into their mother tongue directly. While this translation technique has a weak level of adhesion in memory. The technique of introducing words to students can be through providing context, definitions, synonyms, antonyms, original items, imitations, pictures, demonstrations, and finally translation. Recognition of word meanings in these ways can utilize the development of educational technology with learning media. One variety of learning media that can be used to introduce vocabulary is multimedia. Multimedia that can represent text, sound, images, animation, and video can be an effective alternative learning media. In the hope that it can increase students' enthusiasm for learning and make learning more enjoyable. Therefore, this article describes Arabic vocabulary learning techniques and the use of interactive media as a means of learning Arabic vocabulary.